Menggunakan Metode UEQ+ Dalam Menganalisis Dan Mengevaluasi Pengalaman Pengguna Mobile JKN - Zulpa Salsabila; Fandi Halim; Ronaldi Damanik; Talenta Purnama Cinta (JSAI (Journal Scientific and Applied Informatics), 2024)
Through this user experience analysis and evaluation, we can find out how much the JKN Mobile application is worth, based on the assessment of the use of the application. This study uses the User Experience Questionnaire plus (UEQ +) method where UEQ + has the advantage of Creating questionnaires with UX aspects that can be selected according to the needs of various scales in the product to be evaluated. UEQ + also uses Microsoft Excel to analyze the questionnaires obtained. As an Online Questionnaire, the scale used in UEQ + is no more than 6 scales considering that it is important to keep the length of the questionnaire within a reasonable range to get a reasonable response rate. UEQ + also has several measurement dimensions such as Trust, Dependability, Content Quality, Trustworthiness of Content, Efficiency, Clarity, Intuitive Use, Value, and Usefulness. The results of this study found that as a type of application for Medical is good, the KPI value of the 9 scales gets results greater than the standard deviation value which indicates that JKN Mobile is considered very good by respondents.